2019
DOI: 10.1177/1071100719890854
|View full text |Cite
|
Sign up to set email alerts
|

Three-Stage Masquelet Technique and One-Stage Reconstruction to Treat Foot and Ankle Tuberculosis

Abstract: Background: The purpose of this article was to report the feasibility and effectiveness of 3-stage Masquelet technique and 1-stage operation for different stages of foot and ankle tuberculosis (TB). Methods: Ten consecutive patients with foot and ankle TB were retrospectively analyzed between January 2014 and December 2018. Five patients were treated with the 3-stage Masquelet technique, including thorough debridement with vacuum sealing drainage, implantation of antibiotic cement spacer, and subsequent recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It could successfully control or eradicate bone infection and facilitate defect reconstruction. Its effectiveness for treating infectious bone defects in the lower extremity had been testified 20 . High‐concentration antibiotics locally released from bone cement effectively interfere with bacterial colonization and bacterial membrane formation.…”
Section: Discussionmentioning
confidence: 99%
“…It could successfully control or eradicate bone infection and facilitate defect reconstruction. Its effectiveness for treating infectious bone defects in the lower extremity had been testified 20 . High‐concentration antibiotics locally released from bone cement effectively interfere with bacterial colonization and bacterial membrane formation.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51] Patients are generally only partially weightbearing while the PMMA spacer is in place. [48][49][50][51] Therefore, for the application of the PMMA composite as a temporary spacer, a slightly decreased compressive strength upon implantation does not prohibit its used in this application. Additionally, since PMMA composites continually strengthen over time (see Figures S2 and S3, Supporting Information), possibly reflecting reaction of residual monomers and/or oligomers, the PMMA/10wt%CD-DOX and PMMA/15wt%CD-DOX exceed the 70 MPa threshold over time following implantation.…”
Section: Mechanical Compressive Strength Analysismentioning
confidence: 99%
“…48 h post-fabrication, plain PMMA and PMMA/1.25wt%Free-DOX exceeded the 70 MPa threshold, whereas PMMA/15wt%CD-DOX fell slightly short of this cutoff (by 6.6 MPa). Nevertheless, weight-bearing following the placement of the temporary spacer is highly dependent upon the location of the spacer, size of the defect, and if the spacer is supported with any metallic hardware [48][49][50][51]. Patients are generally only partially weightbearing while the PMMA spacer is in place [48][49][50][51].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research shows that vacuum sealing drainage (VSD) treatment can be effective in promoting the healing of TB wounds with sinus tracts 18,19 . Moreover, a recent study showed the benefits of applying the three‐stage Masquelet technique (debridement with VSD, antibiotic cement spacer, and subsequent reconstruction) in TB of the foot and ankle with sinus tracts 20 . Importantly, stimulation by negative pressure can promote cell viability in polymorphonuclear neutrophils (PMNs) and macrophages to trigger inflammatory responses and induce epithelialization during wound healing 21 .…”
Section: Introductionmentioning
confidence: 99%